Analysis of the SIKEPO Application During the Covid-19 Pandemic - Ramaini Ramaini; Eko Priyo Purnomo; Suswanta Suswanta (Universitas Dharma Wacana, 2022)
ABSTRACTThe purpose of this study was to analyze and describe the effect of the electronic application SIKEPO (Online Employee Attendance Information System) from the rule set 2 times a day attendance then changed to 4 times. This study uses explanatory research with a mix-method approach. The data collection process was carried out by distributing questionnaires and also direct interviews with respondents who were selected by random samplingâ€”testing the data using SEM-PLS. The measurement model is studied through two subs, namely the first: through the outer model. The external model with measurements was assessed through Cronbach alpha and composite reliability. Second, the inner model is studied through the Coefficient of determination (R2 )and the path coefficient. After the 2 sub-tests were carried out, was continued hypothesis testing as well. The results of this hypothesis test indicate that the SIKEPO electronic presence variable has a positive and significant effect on improving the performance of civil servants during the Covid-19 pandemic, so the hypothesis is accepted. Furthermore, the application of electronic SIKEPO does not have a positive and significant effect on improving the work discipline of civil servants during the Covid-19 pandemic, so the hypothesis is rejected. Where the work discipline variable has a T statistic of 0.403 where the value is lower than the standard T statistic of 1.96, besides the P value of 0.687, the hypothesis is rejected.Keywords: SIKEPO; Performance; Work Discipline; Civil Servants; and Covid-19Â